Environmental factors affecting learners' autonomy in the covid-19 pandemic - Wahyu Pratama; Rahayu Kuswardani (Journal of Research on English and Language Learning (J-REaLL), 2021)
Recently, Covid-19 has threatened the education sector and forced  learners to adjust an online learning. According to that, learners need to study in their own space and make them more independent and autonomous. However, learners tend to experience difficulties caused by their surrounding environments that sometimes does not support online learning. Surrounding environments include human activities e.g., noise in the surrounding; financial capabilities of parents for internet data plans; or other issues beyond the student's intellectual abilities. Therefore, this research aimed to explore the existed environmental factors that affected the learning environment and define the factors which affected learners' volition. This study was applied a qualitative method and presenting the collected results descriptively. The researcher worked with one English teacher who has been voluntarily participating in this study. This study used semi-structured interview and questionnaire as the research instruments. Firstly, the researcher sent the questionnaires using Google Form for all students at 11th graders from one of the government-owned senior high schools in Surabaya. Secondly, the researcher interviewed an English teacher to find out the class' conditions. This study has revealed that teacher still holds huge responsibilities to guide students along the online learning process. Besides, there were still a lacks IT skills of students which make the teacher not only a facilitator but also a helper or counsellor. This dominant role of the teacher eventually made students less autonomous.